Adaptive study design to assess effect of TRPV4 inhibition in patients with chronic cough. Issue 3 (2nd August 2021) - Ludbrook, Valerie J.; Hanrott, Kate E.; Kreindler, James L.; Marks-Konczalik, Joanna E.; Bird, Nick P.; Hewens, Debbie A.; Beerahee, Misba; Behm, David J.; Morice, Alyn; McGarvey, Lorcan; Parker, Sean M.; Birring, Surinder S.; et al.
Objective: Airway sensory nerves involved in the cough reflex are activated by adenosine triphosphate (ATP) agonism of P2X purinoceptor 3 (P2X3) receptors. Transient receptor potential vanilloid 4 (TRPV4) channel activation causes ATP release from airway cells, and it is hypothesised that a TRPV4-ATP-P2X3 axis contributes to chronic cough. An adaptive study was run to determine if TRPV4 inhibition, using the selective TRPV4 channel blocker GSK2798745, was effective in reducing cough. Methods: A two-period randomised, double blinded, placebo-controlled crossover study was designed with interim analyses for futility and sample size adjustment. Refractory chronic cough patients received either GSK2798745 or placebo once daily for 7 days with a washout between treatments. Pharmacokinetic samples were collected for analysis of GSK2798745 at end of study. The primary end-point was total cough counts assessed objectively during day-time hours (10 h) following 7 days of dosing. Results: Interim analysis was performed after 12 participants completed both treatment periods. This showed a 32% increase in cough counts on Day 7 for GSK2798745 compared to placebo; the pre-defined negative criteria for the study were met and the study was stopped. At this point 17 participants had been enrolled (mean 61 years; 88% female), and 15 had completed the study. Final study results for posterior median cough counts showed a 34% (90% credible interval: −3%, +85%) numerical increase for GSK2798745 compared to placebo. Conclusion: There was no evidence of an anti-tussive effect of GSK2798745. The study design allowed the decision on lack of efficacy to be made with minimal participant exposure to the investigational drug. Adaptive study design allowed the effect of TRPV4 inhibition on chronic cough to be explored and stopped for futility after only 17 participants. This approach could be used more to limit the exposure of participants to ineffective investigational drugs. https://bit.ly/3wdl4H9